O discurso sobre a crise e a poesia de Marcos Siscar - Carmo, Mariana Nascimento do (2014)
This study, which is based on poet-critic Marcos Siscar in his Interior via satélite, approaches questions related to the Crisis of Verse in Siscar’s poetry. For that, we trace the historical path of the verse itself, to confirm its existence in Siscar’s texts. Making use of the discussions from French poet Stéphane Mallarmé, who first saw in the Crisis of Verse the possibilities of new models for the classical verse. Poet Charles Baudelaire is also important for our discussions, once he has published, in 1869, Pequenos poemas em prosa, a milestone for a new way to think and make poetry. Since he is a poet from our time, other questions, regarding the crisis of the literature itself or even about the quality of the contemporary production, are raised along this essay. This study is divided in three chapters; the first discusses theoretical aspects of the crisis; the second talks about the staging or not in Siscar’s verses; and the third that, from interviews granted by Siscar, works with his verses in an autobiographical way.